A két világháború közötti német történettudomány közelítése Köztes-Európa népeinek vizsgálatához - Orosz, László (Közép-Európai Közlemények, 2014)
The outcome of World War I has forced German historians to reevaluate the role of the histories of the Weimar and National Socialist eras when assessing the history of the Middle European region that had existed between the German and Russian empires. More precisely when assessing the territorial losses of the German Empire and the collapse of the Monarchy over the Danube, which had placed large swathes of German"populated land under foreign rule, and which had transformed their living conditions. For the Germans, the outcome of World War I could be traced back not only to their political and military defeat, but also to their eastern neighbors’ successful scientific endeavors, whose national histories had played a major role in the fight against the imperial integrationist ideology that collapsed in 1918, and which, at the Paris Peace Conference, had had a major influence on where the new eastern"central borders would be drawn. During the 1920’s, German researchers from various disciplines outlined as their goal – in an attempt to protect the German populations of Eastern Europe – the proffering of the intellectual supports on which to build the revisionist pursuits of a defeated Germany. The Ostforschung as a result became a substantial support for German diplomacy’s push to redraw the eastern borders.